Individualisation and Differentiation in secondary English classes: focus on talented learners - Sedláková, Linda (Univerzita Pardubice, 2016)
This thesis aims to analyse and focus on individualisation and differentiation of high-level pupils in common heterogeneous English classes. Action research, carried in lower secondary school, aims to increase an inner differentiation in common English classes. The theoretical part focuses on defining the terms talented or gifted, with further focus on four most common types of conception of the matter. The part continues by specifying a closely related term underachievers followed by several possible ways of a reform, with the focus on inner differentiation. The final part of this paper summarizes practical teaching ideas for an individualisation and inner differentiation of high-level pupils into common classes. The main idea of the inner differentiation is to extend the curriculum of talented pupils with the aim to develop and deepen their knowledge effectively in common English classes to its possible extent.
Individualizace a Diferenciace v hodinách angličtiny : zaměření na talentované žáky
Keywords: Individualizace; vnitřní diferenciace; heterogenní třída; nadaní a talentovaní žáci; podvýkonní nadaní; nerozvinutý talent; Individualisation; inner differentiation; heterogeneous class; gifted and talented pupils; talented underachievers